2023
DOI: 10.1002/fsn3.3290
|View full text |Cite
|
Sign up to set email alerts
|

Trait profiling and genotype selection in oilseed rape using genotype by trait and genotype by yield*trait approaches

Abstract: Selection and breeding for high‐yielding in oilseed rape have always been one of the leading objectives for oilseed rape breeders. This process becomes more complicated when all quantitative traits are considered in selection in addition to grain yield. In the present study, 18 oilseed rape genotypes along with 2 check cultivars (RGS003 and Dalgan) were evaluated across 16 environments (a combination of 2 years and eight locations) in the tropical climate regions of Iran during 2018–2019 and 2019–2020 cropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This emphasizes the need for multi‐environment trials to assess trait stability and adaptability across different growing conditions. Consistent with current literature, the present study identified significant genotypic variation in all the studied traits, indicating the presence of high genetic diversity among the tested oilseed rape genotypes (Bakhshi, Amiri Oghan, Rameeh, Zeinalzadeh Tabrizi, et al., 2023 ). Genetic variation serves as the foundation for selecting superior genotypes with desirable traits and is instrumental in breeding programs aimed at improving oilseed rape.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This emphasizes the need for multi‐environment trials to assess trait stability and adaptability across different growing conditions. Consistent with current literature, the present study identified significant genotypic variation in all the studied traits, indicating the presence of high genetic diversity among the tested oilseed rape genotypes (Bakhshi, Amiri Oghan, Rameeh, Zeinalzadeh Tabrizi, et al., 2023 ). Genetic variation serves as the foundation for selecting superior genotypes with desirable traits and is instrumental in breeding programs aimed at improving oilseed rape.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study align with previous research highlighting the significant influence of environmental factors on the performance of studied traits in oilseed rape (Perveen et al., 2005 ; Tuncturk et al., 2005 ). Environmental effects on traits such as days to flowering, days to maturity, and yield have been reported in recent studies as well (Bakhshi, Amiri Oghan, Rameeh, Fanaei, et al., 2023 ; Bakhshi, Amiri Oghan, Rameeh, Zeinalzadeh Tabrizi, et al., 2023 ). This emphasizes the need for multi‐environment trials to assess trait stability and adaptability across different growing conditions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation